2003
DOI: 10.1182/blood-2002-09-2802
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of alemtuzumab (anti-CD52 monoclonal antibody) in patients with advanced mycosis fungoides/Sézary syndrome

Abstract: This phase 2 study evaluated the safety and efficacy of alemtuzumab in 22 patients with advanced mycosis fungoides/ Sé zary syndrome (MF/SS). Most patients had stage III or IV disease, reduced performance status, and severe itching. The overall response (OR) rate was 55%, with 32% of patients in complete remission (CR) and 23% in partial remission (PR). Sé zary cells were cleared from the blood in 6 of 7 (86%) patients, and CR in lymph nodes was observed in 6 of 11 (55%) patients. The effect was better on eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
226
4
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(253 citation statements)
references
References 43 publications
(50 reference statements)
15
226
4
8
Order By: Relevance
“…Similar results, with no infectious complications, were recently reported in a small cohort of patients treated with modified, low-dose, subcutaneous alemtuzumab for 6 weeks [321]. In addition to hematologic toxicity, conventionally dosed alemtuzumab in advanced-stage MF/SS is associated with a high incidence of infectious complications [319,320,[322][323][324][325]. Overall, infectious complications have been observed in twothirds of treated patients, most of which are bacterial, including sepsis.…”
Section: Monoclonal Antibodiessupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results, with no infectious complications, were recently reported in a small cohort of patients treated with modified, low-dose, subcutaneous alemtuzumab for 6 weeks [321]. In addition to hematologic toxicity, conventionally dosed alemtuzumab in advanced-stage MF/SS is associated with a high incidence of infectious complications [319,320,[322][323][324][325]. Overall, infectious complications have been observed in twothirds of treated patients, most of which are bacterial, including sepsis.…”
Section: Monoclonal Antibodiessupporting
confidence: 82%
“…Alemtuzumab is a humanized IgG1 monoclonal antibody directed against CD52, an antigen widely expressed by B-cells, T cells, and monocytes [318]. In a phase II study in 22 patients with advanced-stage MF/SS, overall and complete response rates of 55 and 32%, respectively, were observed, with a median time to treatment failure of 1 year [319]. Given the significant risk of infectious complications, low-dose subcutaneous alemtuzumab was investigated in 14 patients with SS, most of whom had relapsed/refractory disease [320].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Lundin and colleagues conducted a phase II study of alemtuzumab in 22 patients with advanced MF/SS. 74 The ORR was 55%; 32% of patients achieved a CR and 23% a PR. Sé zary cells were cleared from the blood in 6 of 7 (86%) patients, and CR in lymph nodes was observed in 6 of 11 (55%) patients.…”
Section: Chemotherapy Many Different Chemotherapeuticmentioning
confidence: 91%
“…73 Alemtuzumab is usually administered at a dose of 30 mg intravenously three times per week, following an initial dose-escalation phase, for up to 12 weeks. 30,74 In studies in patients with MF/SS to date, the most common adverse events were opportunistic infections and neutropenia, which can be severe. 30,74 Recently, Lenihan and colleagues suggested that severe cardiotoxicity may be a significant complication of alemtuzumab treatment in MF/SS.…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation